Status Penguasaan Tanah Reklamasi Untuk Pemukiman Penduduk Lokal Studi Di Pulau Bungin, Kecamatan Alas, Kabupaten Sumbawa - Nurmawanti, Nunung; Rahman, Arief (Fakultas Hukum Universitas Mataram, 2024)
The purpose of the study is to find out and discuss the status of ownership of land reclamation for residents' settlements by taking research on Bungin Island, Alas District, Sumbawa Regency. The legal method the author uses in this research is the empirical legal research method. This research uses a statutory approach, a conceptual approach, and a sociological approach. The results of this study show that residents on Bungin Island carry out reclamation in 2 (two) ways, namely: traditional/natural reclamation and modern reclamation. Most of the residents who control land resulting from reclamation have been certified as an Ownership. The land Certificates issued on Bungin Island have amounted to 700 (seven hundred) certificates. The obstacle land reclamation process on Bungin Island is regarding territorial boundaries, because they claim each other and they are lack of awareness among residents regarding the importance of having a land certificate. The efforts made by the village government are to continue to provide socialization to residents for making a land certificate is very important. Furthermore, the village government can facilitate its residents who want to obtain a certificate of ownership rights.